2021
DOI: 10.3390/microorganisms9091928
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Based Taxonomic Classification, and Comparative Genomic Analysis of Potentially Human Pathogenic Enterobacter spp. Isolated from Chlorinated Wastewater in the North West Province, South Africa

Abstract: Comparative genomics, in particular, pan-genome analysis, provides an in-depth understanding of the genetic variability and dynamics of a bacterial species. Coupled with whole-genome-based taxonomic analysis, these approaches can help to provide comprehensive, detailed insights into a bacterial species. Here, we report whole-genome-based taxonomic classification and comparative genomic analysis of potential human pathogenic Enterobacter hormaechei subsp. hoffmannii isolated from chlorinated wastewater. Genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
3
0
2
Order By: Relevance
“…Taxonomic assignment of the isolates was based on dDDH, and ANIb, which were in congruence (A3 and A4 in S1 Data ). Whole genome sequencing-based phylogenomic analyses greatly improves the identification of isolates through the elucidation of functional profiles of taxonomic groups, and this can resolve ambiguities in the phylogeny of higher taxa, that would be difficult using traditional approaches [ 8 , 9 , 50 ]. Of the four designated clades, only the P. syringae species complex clade is known to include plant pathogenic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Taxonomic assignment of the isolates was based on dDDH, and ANIb, which were in congruence (A3 and A4 in S1 Data ). Whole genome sequencing-based phylogenomic analyses greatly improves the identification of isolates through the elucidation of functional profiles of taxonomic groups, and this can resolve ambiguities in the phylogeny of higher taxa, that would be difficult using traditional approaches [ 8 , 9 , 50 ]. Of the four designated clades, only the P. syringae species complex clade is known to include plant pathogenic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Current taxonomy and identification improvements have focused on using whole genome alignments instead of 16S sequences, particularly for pathogen outbreak tracking and variant differentiation [37, 38]. Some techniques make use of solely vertically transferred genes, which illustrates a choice of genes for phylogenetics [39].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that all strains of pond species were considered multidrug resistant and could lead to the emergence of ESBL bacteria, posing a threat to human health upon exposure. Furthermore, nanopore sequencing technology has also been applied to industrial wastewater, [ 93 ] activated sludge, [ 94 ] animal husbandry, [ 95 ] medical waste, [ 96 ] and other environments.…”
Section: Nanopore Sequencing Technology For Microorganisms Detectionmentioning
confidence: 99%